2018
DOI: 10.1101/346163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IQGAP3 Overexpression Correlates with Poor Prognosis and Radiation Therapy Resistance in Breast Cancer

Abstract: Background: IQ motif-containing GTPase activating 24 protein 3 (IQGAP3), the latest found protein of IQGAP family, 25 may act as a crucial factor in the process of cancer development 26 and progression; however, its clinical value in breast cancer 27 remains unestablished so far. Our team explored the correlation 28 between IQGAP3 expression profile and the clinicopathological 29 features in breast cancer. Methods: IQGAP3 levels in breast 30 cancer cell lines and tumor tissues were detected by real-time 31 PCR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…IQGAP3 is a newly discovered IQGAP and has been found to be overexpressed in BC tissues in our previous studies [20,32]. In the present study, we found that the high expression of IQGAP3 in BC cells was significantly reduced by natural phytochemicals, especially Kaempferol.…”
Section: Discussionsupporting
confidence: 69%
“…IQGAP3 is a newly discovered IQGAP and has been found to be overexpressed in BC tissues in our previous studies [20,32]. In the present study, we found that the high expression of IQGAP3 in BC cells was significantly reduced by natural phytochemicals, especially Kaempferol.…”
Section: Discussionsupporting
confidence: 69%
“…This manuscript has been released as a preprint at bioRxiv ( Hua et al, 2018 ) and the abstract of this manuscript has been accepted as an oral presentation in ESMO ASIA annual meeting 2018. We would like to thank the native English speaking scientists of Elixigen Company (Huntington Beach, California) for editing our manuscript.…”
mentioning
confidence: 99%